Pengaruh Motivasi Anggota Terhadap Partisipasi dalam Koperasi Merah Putih - Fahri Azizi; Hendra Riofita (MANAJEMEN, 2026)
This study aims to analyze the influence of member motivation on participation in the Merah Putih Cooperative. The method used in this research is a literature study by reviewing various sources such as scientific journals, books, and other relevant references. The results of the study indicate that member motivation has a significant influence on the level of member participation in cooperatives. This motivation consists of intrinsic motivation, such as awareness, sense of belonging, and responsibility, as well as extrinsic motivation, such as economic benefits, service quality, and incentives provided by the cooperative. The findings show that intrinsic motivation has a more dominant influence in encouraging member participation compared to extrinsic motivation. In addition, supporting factors such as cooperative education, management transparency, and effective communication also strengthen member motivation. Therefore, increasing member motivation is a key factor in improving member participation and ensuring the sustainable success of cooperatives. This study is expected to contribute to the development of cooperative economics and serve as a reference for cooperative managers in formulating strategies to enhance member participation